EDUCATIONAL PROGRAMS THROUGH TECHNOLOGIES USE BY OPEN AND DISTANCE LEARNING SYSTEM AT COASTAL REGIONS, OPEN DISTANCE LEARNING UNIT OF JEMBER, EAST JAVA PROVIENCE, INDONESIA (CASE STUDY AT OPEN DISTANCE LEARNING UNIT OF JEMBER, INDONESIA): educational programs, technologies use, open and distance learning system - Isdianto, Joko (STISOSPOL WASKITA DHARMA, 2017)
Recently, day by day The Technology always helps so many people in the world whatever their fields and wherever they want to do. One of the mainly benefits of the technology are increasing the teaching and learning capacities of the Open and Distance Learning System at The Coastal Region, such as Open and Distance Educational Program at Jember regency. Technologies here are the main support for the educational development in the most coastal regions in Indonesia. Many people use the advanced technologies, such as internet, as the main wares of the educational development. They promote the using of internet in many schools in Indonesia, specially in coastal regions, such as coastal regions in Java Island, such as Jember, Banyuwangi, Situbondo and Probolinggo Regency. Today, most of the students in such coastal regions always have fun in their study with internet as the advanced technology. Technologies have enchaned teaching and learning distance method in Indonesia, Specially in coastal region. Many Students in this coastal area have used advanced technologies, such as computer in the classroom, new website, interactive key board, Blog and wikis, in this case, Web 2.0 that implemented in the class, so many students can have much more dialogues, digest dialogues, ideas and brainstorming. Beside, such as a wireless michrophone, a mobile and digital game, also to be the other alternatives maintenance of the advanced technologies in enchanced teaching and learning system. Distance educational system by using advanced technologies make the goal of international education system become more achievable and more accessible to all students at Coastal Region. Here, Technologies have more contributions to the enchanced teaching and learning system, like what display in this site: http://www.slideshare.net/NASuprawoto/penggunaan-internet-dalam-pembelajaran-matematika-di-sd.. We can analyze ODL use at other coastal area beside Jember, such as Probolinggo, Situbondo and Banyuwangi, from the datas that has been collected at Open Distance Learning Unit office of Jember. Because Probolinggo, Situbondo and Banyuwangi are conquered by ODL Unit office of Jember, East Java, Indonesia. So, the centre of ODL System at east coastal area of east Java are stated at Jember Regency.So, the centre of ODL System at east coastal area of east Java are stated at Jember Regency. The method we use for this research is a Triangulasi Method with population and sample are taken at listed students of Jember ODL Unit Office, are covering Situbondo, Probolinggo, and Banyuwangi. Here, Online tutorials are the most favourable mechanisms for providing education through Open and Distance Learning System all over the world. Online tutorial always give the students so many things and choices for learning, beginning from the materials of studies, the choices of books shopping, various literatures at online library, various kind of friends for communicating between one student to another. So, Technologies and Online Learning Strategies can provide education through Open and Distance Learning System at Remote Regions in Indonesia.